1989
DOI: 10.1002/bip.360281111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nucleotide bromination on the stabilities of Z‐RNA and Z‐DNA: A molecular mechanics/thermodynamic perturbation study

Abstract: The structures of ZI- and ZII-form RNA and DNA oligonucleotides were energy minimized in vacuum using the AMBER molecular mechanics force field. Alternating C-G sequences were studied containing either unmodified nucleotides, 8-bromoguanosine in place of all guanosine residues, 5-bromocytidine in place of all cytidine residues, or all modified residues. Some molecules were also energy minimized in the presence of H2O and cations. Free energy perturbation calculations were done in which G8 and C5 hydrogen atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…However, these bands almost disappear from the SERS of ds br C5. It has been shown that the C5‐bromination has little effect on the atomic charge distribution of cytosine19 as well as on the overall duplex stability 1920. Thus, we deduce that in the duplex conformation the NH 2 group geometry is largely determined by the strong Watson–Crick base pairing which significantly reduces the influence of the Br group on the amino conformation (see Supporting Information, Figure S10, for a more detailed discussion).…”
mentioning
confidence: 68%
“…However, these bands almost disappear from the SERS of ds br C5. It has been shown that the C5‐bromination has little effect on the atomic charge distribution of cytosine19 as well as on the overall duplex stability 1920. Thus, we deduce that in the duplex conformation the NH 2 group geometry is largely determined by the strong Watson–Crick base pairing which significantly reduces the influence of the Br group on the amino conformation (see Supporting Information, Figure S10, for a more detailed discussion).…”
mentioning
confidence: 68%
“…The FEP approach has been employed by Kollman's group in the estimation of the change in ⌬G B→Z caused by certain modifications of the DNA sequence. [36][37][38] However, the actual free energy change of the B-to Z-DNA transition cannot be computed by this method due to the dissimilarity of the conformers which results in insurmountable sampling problems. Even with an extremely simplified DNA model, a direct estimation of ⌬G B→Z through the FEP method would require the simulation of a huge number of intermediate models, which is exceedingly expensive in terms of computer time.…”
Section: The Thermodynamic Path For the Computation Of The Free Ementioning
confidence: 99%
“…The shifts in equilibrium between B and Z conformations occur due to the steric hindrance of bromo-substitution at the C8 position. Moreover, the substitution of the bromo group interacts with the phosphate backbone of the DNA to form a syn conformation [93][94][95].…”
Section: C8-brominationmentioning
confidence: 99%